SELF-MANAGEMENT DAN DUKUNGAN KELUARGA PADA LANJUT USIA DENGAN PENYAKIT KRONIS - Ilmi, Ani Auli; Fatimah, Nurul; Patima, Patima (Journal of Islamic Nursing, 2018)
Chronic illness is a long-term health disorder and cannot be cured without definitive treatment, requires lifelong support and care. In the elderly there is a decline in cells due to the aging process which can cause various diseases including chronic diseases. Chronic illness Not only causes pain, death, and physical disability of sufferers, but also a long treatment procedure can cause sufferers to experience psychological stress and feel hopeless. So that good family support is needed which can further improve good self-management in patients. Therefore, the authors are interested in conducting a literature study to determine the effect of self-management and family support on age and chronic illness. This type of writing is a literature review using Google Scholar and Garuda Portal. Then after the identification, screening and feasibility process, there are 4 national literature, 2 international literature and 1 text book that fits the inclusion criteria. Based on the results of the seventh literature, it can be concluded that there is a positive influence on self-management and family support on the handling of the elderly with chronic diseases. Both are interconnected, clients with chronic diseases can trust and use self-management well when they get support from a good family. Therefore elderly people with chronic diseases and families are expected to be able to apply this to be one of the actions in dealing with chronic diseases.